Subject-activity model in forming officer’s leadership competence in the Academy of Ground Forces of Ukraine - BOYKO, Oleg (Journal of Education, Technology and Computer Science, 2013)
Thus, we defined the essence of leadership competency of the future officerand exposed parts of didactic model of its formation, based on the concept ofsubject-activity training of military specialists and implemented in the educationalprocess of the Academy of Armed Forces named after hetman PetroSagaydachnyi (see scheme 2).Prospects for further researches can be: justification and development ofmethods of leadership competence formation of officers in schools and experimentalverification of its effectiveness.